Optically transparent boron-doped nanocrystalline diamond films for spectroelectrochemical measurements on different substrates. Issue 1 (January 2016) - Sobaszek, M.; Siuzdak, K.; Skowroński, Ł.; Bogdanowicz, R.; Pluciński, J.
Abstract: Fabrication process of optically transparent boron nanocrystalline diamond (B- NCD) electrode on silicon and quartz substrate was shown. The B-NCD films were deposited on the substrates using Microwave Plasma Assisted Chemical Vapor Deposition (MWPACVD) at glass substrate temperature of 475 °C. A homogenous, continuous and polycrystalline surface morphology with high sp 3 content in B-NCD films and film thickness depending from substrate in the range of 60-300 nm was obtained. The high refraction index and transparency in visible (VIS) wavelength range was achieved. Moreover, cyclic voltammograms (CV) were recorded to determine reaction reversibility at the B-NCD electrode. CV measurements in aqueous media consisting of 1 mM K3 [Fe(CN)6 ] in 0.5 M Na2 SO4 demonstrated relatively fast kinetics expressed by a redox peak splitting below 503 mV for B-NCD/silicon and 110 mv for B-NCD/quartz.